Relative price and inflation uncertainty in Colombia: A case of chronic moderate inflation 1970-1990 - Clavijo, Sergio (Estudios Económicos de El Colegio de México, 1994)
This study explores two aspects of Colombian chronic but moderate inflation experience during the period 1970-1990. Based on time series analysis, the study suggests that the policy to increase relative price of energy products be complemented with expenditure reducing mechanisms to avoid the validation of higher price pressures stemming from other sectors. Moreover, it recommends efforts to dismantle indexation mechanisms , which make it difficult to reduce inflation.